Implementasi Pendidikan Akhlak Perspektif Al-Ghazali dalam Pembinaan Karakteristik Peserta Didik - Dena Aulia Harani; Nikki Azyati; Ukhty Mumtaza (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Moral education has become an urgent need amid the increasing moral degradation of students, such as hedonistic behavior, poor manners, and weak discipline. This condition shows that moral guidance in schools has not comprehensively touched on the realm of inner transformation. Imam Al-Ghazali's thinking, which emphasizes tazkiyatun nafs, mujahadah, riyadhah, and exemplary behavior, offers a more in-depth approach to shaping holistic character. This study aims to describe the concept of morals according to Al-Ghazali, analyze its relevance to modern students, and formulate its implementation in the school context. The research uses a literature study method by analyzing classical books, scientific articles, and the latest research results. The findings show that moral education, according to Al-Ghazali, requires a combination of spiritual strengthening, behavioral training, and consistent habits. Implementation in schools can be done through tazkiyah programs, teacher role modeling, worship habits, moral reflection, and the integration of moral values into school culture. The main argument of the study asserts that Al-Ghazali's approach is more effective in responding to the moral challenges of the digital age because it builds character from the aspects of the heart, behavior, and spiritual awareness simultaneously.   Keywords: Moral education, Al-Ghazali, tazkiyatun nafs, character, modern schools.